An Overview of Microfinance Institutions and Related Developments in Pakistan - Javed, Asif; Khan, Faeyza (Journal of Development Policy Research and Practice (JoDPRP), 2024)
This research work is an attempt to assess the current state of microfinance in Pakistan with a view to collaboratively finding strategic and bespoke solutions to increasing the financial inclusion footprint in the country. Key Informant Interviews (KIIs) have been held with stakeholders across a wide spectrum comprising investors, development agencies, practitioners, apex bodies, credit bureau and regulators so that a candid and consensual approach may emerge with solutions that are practical and implementable. It was pointed out by stakeholders that Pakistan’s financial institutions are well established, and the legislative framework and regulatory structure have nimbly evolved to create sufficient infrastructure for growth across the board. However, there is lack of partnerships among Microfinance Banks and Non-Banks Microfinance Companies. Going forward, financial institutions should focus on digital financial services to expand their network. JEL Classification Codes: G21